2023
DOI: 10.2355/isijinternational.isijint-2022-498
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Water Content Estimation for Wet Granulation of Iron Ore Powders with Quicklime Binder

Abstract: water content () for estimating the optimum water content ( ) was individually defined π‘Š torque π‘Š exp opt for the types I and II. The was well correlated with the , regardless of the type and π‘Š torque π‘Š exp opt blending ratio of the original ore powders and quicklime. Finally, the optimum water content was estimated using the . The estimated water content was confirmed to be in good agreement π‘Š torque with the experimental results, demonstrating that the optimum water content for the wet granulation of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A partition coefficient of iron ore, coke, limestone, and sinter fines was introduced by Litster et al [ 16 ] to arrive at optimum moisture content through a mathematical model. Yokokawa et al [ 17 ] demonstrated agitation torque as an influencing factor in estimating the optimum moisture, with the help of a torque rheometer. Their experimental setup comprised an agitator with a main and an auxiliary blade that is rotated in the green mix being granulated.…”
Section: Introductionmentioning
confidence: 99%
“…A partition coefficient of iron ore, coke, limestone, and sinter fines was introduced by Litster et al [ 16 ] to arrive at optimum moisture content through a mathematical model. Yokokawa et al [ 17 ] demonstrated agitation torque as an influencing factor in estimating the optimum moisture, with the help of a torque rheometer. Their experimental setup comprised an agitator with a main and an auxiliary blade that is rotated in the green mix being granulated.…”
Section: Introductionmentioning
confidence: 99%